Enhancing EFL Learners Diphthong Pronunciation Ability’s using PRAAT - Nurjannah Nurjannah; Nofiana Nofiana; Miftahul Jannah; Farah Farah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
Pronunciation is one of the most important aspects for learners in studying English. Today, pronunciation tends to be neglected by instructors in EFL (English as a Foreign Language) classes, especially for vowel sounds. Computer-assisted language learning (CALL) is one of the alternative methods in enhancing students’ ability in pronunciation. PRAAT is software used to measure the quality of students’ pronunciation. They were able to enhance their pronunciation practice by using the visual spectrogram. The purpose of this research was to determine the efficacy of employing CALL in pronunciation classes. The numbers of students in this research were 30 Acehnese EFL students. The methodology was quantitative through experimental research. A Word list was used as an instrument to obtain data from the learners. Based on the results, there was a significant improvement after the learning process. The learners had difficulty with five significant mistake sounds: [e], [ei], [i], [e], [e]. They recognized these sounds as monophthongs. This inaccuracy was caused by unfamiliarity with English diphthongs, because these sounds did not found in L1 and L2. After a few repetitions, the students began to use more diphthongal and higher F1 and F2 sounds. Hence, it can be concluded that the CALL had a positive impact in enhancing the student’s ability in pronunciation.